Are we born and do we die without nevi? A cross‐sectional study. (17th May 2021) - Di Brizzi, Eugenia Veronica; Pampena, Riccardo; Licata, Gaetano; Calabrese, Giulia; Longo, Caterina; Argenziano, Giuseppe
Abstract: Background: It is well known that the number of nevi varies with age. However, there are a few data in the literature concerning total nevus count at different ages. The aim of this study was to assess and compare the total nevus count among different age groups. Methods: The total nevus count was assessed in consecutive patients belonging to nine age groups. Median nevus count was calculated and compared for each age group. Multivariate logistic regression analysis was used to define the influence of sex and phototype on the association between nevus count and age. Results: We enrolled 900 patients (461, 51.2% females), with a median age of 46 years and a total of 18, 136 nevi. Significant differences were found in the median total nevus count among all age groups ( P < 0.001), with a significant increase in the first two decades and a significant decrease after the age of 50 years. A similar trend was also observed in subgroups. The differences observed in the total body nevus count among age groups were independent of sex and phototype. Conclusions: We demonstrate that the total nevus count significantly increases during childhood and gradually decreases in the elderly.